2022
DOI: 10.3390/ijerph19020798
|View full text |Cite
|
Sign up to set email alerts
|

Results and Strategies for a Diversity-Oriented Public Health Monitoring in Germany

Abstract: Germany is a country of immigration; 27% of the population are people with a migration background (PMB). As other countries, Germany faces difficulties in adequately including hard-to-survey populations like PMB into national public health monitoring. The IMIRA project was initiated to develop strategies to adequately include PMB into public health monitoring and to represent diversity in public health reporting. Here, we aim to synthesize the lessons learned for diversity-oriented public health monitoring and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
0
9
0
3
Order By: Relevance
“…The analysis in this paper has therefore shown that attitudes towards participation in health research are contingent on a range of personal biographies, culturally sanctioned ideals and values, and shaped by the complex intersections of social location and experience. Our anti-categorical and comparative approach as well as our understanding of cultural processes as underlying all social behaviour [ 54 ], rather than simply as a prism for minority ethnic status or ‘hard-to-survey populations’ [ 42 ] makes visible the specific and situated practices informed by both oppression and privilege. Indeed, while some participants identified as migrants or narrated experiences of nativist exclusion, they fully participated in predominant value systems and discursive frames.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis in this paper has therefore shown that attitudes towards participation in health research are contingent on a range of personal biographies, culturally sanctioned ideals and values, and shaped by the complex intersections of social location and experience. Our anti-categorical and comparative approach as well as our understanding of cultural processes as underlying all social behaviour [ 54 ], rather than simply as a prism for minority ethnic status or ‘hard-to-survey populations’ [ 42 ] makes visible the specific and situated practices informed by both oppression and privilege. Indeed, while some participants identified as migrants or narrated experiences of nativist exclusion, they fully participated in predominant value systems and discursive frames.…”
Section: Discussionmentioning
confidence: 99%
“…This was exacerbated by the means of invitation, i.e. sending written letters exclusively in German, known to be ineffective for reaching individuals with insufficient German language skills [ 63 , 42 , 62 ]. Despite justified critique of an ‘ethnic matching’ or ‘race'-of-interviewer-effects’ approach that assumes a one-dimensional and static approach to social location [ 27 ], pairing respondents and interviewers with the same country of origin, ethnicity or language has often been recommended to improve the inclusion of diverse communities [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only by considering this diversity, is it possible to make differentiated statements about the health status of people with a history of migration. Thus, it is necessary not only to compare broadly categorised groups in analyses of public health data, such as people with or without a migration background, but also to consider aspects such as socio-economic situation, duration of residence, reasons for migration, German language proficiency, or experiences of discrimination in a differentiated manner [ 4 ].…”
mentioning
confidence: 99%